Surgery for deep infiltrating rectal endometriosis-Selecting the right approach - Tamyenthini Jeyabalan; Theiyallen Ambikapathi; Sentilnathan Subramaniam; Ratha Krishnan Sriram; Nornazirah Azizan; Firdaus Hayati (John Wiley and Sons Inc, 2022)
Endometriosis involving the bowel is a form of deep infiltrating endometriosis (DIE). The endometriotic lesions can infiltrate the bowel layers mimicking a malignancy. The majority of bowel involvement happens in the colon and rectum. We report our experience in surgically managing rectal endometriosis in two patients, one via a conservative approach and the other with a more radical approach and their associated short-term and long-term outcomes are observed. In principle, surgery remains the mainstay of treatment in managing rectal DIE with adjuvant hormonal therapy. The selection of surgical approach should be based on disease factors such as the size of the lesions and extent of the disease, patient factors including fitness for surgery and expectations as well as logistics and resource limitations.